The Impact of Corporate Social Responsibility on Corporate Value: The Role of Company Size In Indonesia Capital Market - Hersugondo, Hersugondo; Kartika, Andi (Proceeding Fakultas Ekonomi, 2017)
This study outlines aimed to look at the effect of corporate social responsibility on corporate value and effect of Corporate Social Responsibility on the value of the company with the size of the company as a moderating variable. The population of this research consisted of manufacturing companies listed on the Stock Exchange for the following reason: the manufacturing companies had a greater effect on the surrounding environment as a result of the activities of the company. Sample were selected by using a purposive sampling method with the purpose to obtain a representative sample in accordance with the criteria specified. The data were processed by a multiple linear regression analysis (multiple regression analysis). Corporate Social Responsibility rating was based on GRI standards (Global Reporting Initiative), whereas the value of the company used a measuring tool Tobin's Q. The results of this study proved that the variables of Corporate Social Responsibility (CSR) significant positive effect on the value of the company while the variable size (size) of the company as a moderating variable affect the relationship of CSR and corporate value.